Policy Guidelines for Managing Variation Orders in Philippine Water and Wastewater Projects Using Analytical Hierarchy Process - Misael L Camposano Jr; Arvin R De La Cruz; Joseph Raniel A Bianes (Research Synergy Press, 2025)
This study aimed to identify and analyse the impacts of variation orders on project costs in selected water and wastewater projects in the Philippines using the Analytical Hierarchy Process (AHP). Specifically, the study sought to determine and rank the most critical causes of variation orders and to propose a policy guideline to minimize their impacts on project costs. A mixed-methods approach was employed, involving surveys administered to experts directly involved in water and wastewater projects. Responses were evaluated using the AHP technique, which enabled the prioritization of the identified causes based on their relative influence. The results revealed that design changes, errors and omissions in design, and changes in project scope were the top contributing factors to variation. These causes were found to significantly affect project cost, leading to increased expenditures and potential delays. Consequently, the desire for profit and the ambiguous design from the consultant are driving variation, impacting cost as well. Through the AHP, a pairwise comparison matrix was developed, which established a consistent and structured ranking of these causes based on expert judgment. The study concluded that effective planning to finalize the scope, enhanced stakeholder coordination, and improved design review processes are essential to mitigate the adverse impacts of variation orders on the project cost. A policy guideline was developed to assist agencies in managing and reducing variation-related issues in future projects